Perspectives in the development of mobile medical information systems : life cycle, management, methodological approach and application - Keikhosrokiani, Pantea (Academic Press, 2020)
Perspectives in the Development of Mobile Medical Information Systems: Life Cycle, Management, Methodological Approach and Application discusses System Development Life Cycle (SDLC) thoroughly, focusing on Mobile Healthcare Information Systems (M-HIS). Covering all aspect of M-HIS development, the book moves from modeling, assessment, and design phases towards prototype phase. Topics such as mobile healthcare information system requirements, model identification, user behavior, system analysis and design are all discussed. Additionally, it covers the construction, coding and testing of a new system, and encompasses a discussion on future directions of the field.